Tracking key CAADP indicators and implementation processes [In the 2020 ATOR] - Makombe, Tsitsi; Tefera, Wondwosen; Ulimwengu, John M. (International Food Policy Research Institute, 2020)
This chapter discusses progress on 25 of the 38 CAADP RF indicators for which cross-country data are available (Table 16.2)—details of the indicators and aggregate statistics are available in the data tables in Annexes 1–3 of this report. Progress is discussed across different geographic and economic groupings on the continent, comparing trends in the RF indicators since the adoption of CAADP in 2003 (that is, from 2003 to 2019) with the pre-CAADP subperiod (1995 to 2003). In keeping with the policy theme of the 2020 ATOR, this chapter also discusses recent policy adjustments due to the COVID-19 pandemic in selected African countries. Starting with the next section, the chapter also discusses the CAADP implementation process itself in terms of country and regional progress in developing evidence-based, Malabo-compliant national agriculture investment plans (NAIPs) and operationalizing CAADP mutual accountability processes to support agriculture sector review and dialogue.